2019
DOI: 10.18553/jmcp.2018.18058
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Through Migraine Preventive Treatments: Implications for All-Cause Total Direct Costs and Disease-Specific Costs

Abstract: Eli Lilly and Company was the sole sponsor and funder for this study and was responsible for the study design, data collection, data analysis, interpretation of data, and decision to publish the findings. All authors are employees and minor stockholders of Eli Lilly and Company. Nyhuis was employed by Eli Lilly and Company at the time of this study. The findings of this study were presented in part at the 18th Congress of the International Headache Society; September 7-10, 2017; Vancouver, Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Adherence with traditional migraine preventive therapies is generally low, with approximately 77% to 85% of patients discontinuing their initial migraine preventive medication within 1 year [7,8]. Patients who discontinue or switch preventive treatments experience a substantial burden in terms of impaired function and quality of life [9], as well as increased healthcare resource utilization and costs [7]. The most common reasons for discontinuation include lack of efficacy and poor tolerability [10].…”
Section: Introductionmentioning
confidence: 99%
“…Adherence with traditional migraine preventive therapies is generally low, with approximately 77% to 85% of patients discontinuing their initial migraine preventive medication within 1 year [7,8]. Patients who discontinue or switch preventive treatments experience a substantial burden in terms of impaired function and quality of life [9], as well as increased healthcare resource utilization and costs [7]. The most common reasons for discontinuation include lack of efficacy and poor tolerability [10].…”
Section: Introductionmentioning
confidence: 99%
“…8 Oral preventive medications for migraine have been associated with suboptimal efficacy or intolerable side effects that frequently lead to poor adherence, multiple medication switches, or discontinuation; 5,6,9 as a result, many patients rely solely on acute medications for treatment of their migraine attacks. 11 Galcanezumab is a humanized monoclonal antibody that potently and selectively binds to the CGRP ligand 12,13 and is approved for the preventive treatment of migraine in adults. 10 A recent study evaluated cycling of preventive migraine medications from a claims database and found that for patients with episodic and chronic migraine, more than 75% of patients switched or discontinued their initial preventive treatment within 12 months, leading to increased healthcare resource utilization and cost.…”
Section: Introductionmentioning
confidence: 99%
“…10 A recent study evaluated cycling of preventive migraine medications from a claims database and found that for patients with episodic and chronic migraine, more than 75% of patients switched or discontinued their initial preventive treatment within 12 months, leading to increased healthcare resource utilization and cost. 11 Galcanezumab is a humanized monoclonal antibody that potently and selectively binds to the CGRP ligand 12,13 and is approved for the preventive treatment of migraine in adults. 14,15 The efficacy, safety, and tolerability of galcanezumab for migraine prevention have been established in 2 Phase 2 studies 16-18 and 3 Phase 3 studies.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of effectiveness and intolerability often result in multiple medication switches, poor adherence or discontinuation . A recent study in patients with episodic or chronic migraine reported that >75% of patients switched or discontinued their initial preventive treatment .…”
Section: Introductionmentioning
confidence: 99%